Fem simulation study of photonic nanojets using ellipsoids - Muhammad Amsyar Mohd Faisal (2017)
Photonic Nanojet generation using a microsphere have been studied for years. Other methods, such as multilayered microspheres, truncated microspheres and microcubes, have been explored. However, little research has been done into the use of ellipsoids for producing a photonic nanojet. In this study, a 2D FEM simulation method was employed to achieve a nanojet with high Q-value using an ellipsoid. Optical parameters such as the wavelength of the illumination beam, the refractive index and the numerical aperture were varied. The results obtained from using the ellipsoid were compared with that of a microsphere. The size of the ellipsoid were also varied. The Q-value and working distance of the photonic nanojets generated were calculated, tabulated and studied. From the results, a nanojet with Q-value up to 0.3462 was achieved. It was also shown that using an ellipsoid could provide a better nanojet working distance than when using a microsphere. The highest obtainable working distance was found to be 26136 nm (~49λ) and the smallest width obtained was 355 nm.